Study on the Health Status of Coastal People in Bangladesh After Cyclone Sidr and Aila - Kabi, Russell; Khan, Hafiz T. A. (European Scientific Journal, ESJ, 2017)
Bangladesh is recognized as one of the high-risk countries in the world that is prone to natural disasters. Due to its geographical location, topography, high population density, poverty and lower adaptive competence it is considered to be highly vulnerable to natural disasters in the world. This study was devised following the super cyclone Sidr that hit Bangladesh in November 2007 and cyclone Aila that hit in May 2009 to assess the impact of extreme weather event like cyclone on health of the coastal population of Bangladesh. A total of approximately 1000 households were selected by using the multistage cluster sampling technique from both villages. The study result shows that diarrheal, skin disease and mental health problems increased after the cyclones. The multivariable analysis shows that age of the respondents, gender, monthly income and educational level of the household heads and number of living children in the family have statistically significant effect on causing health problems before and after the cyclone Sidr and Aila. It can be concluded that extreme weather events like cyclones Sidr and Aila making the lives of the coastal people more difficult and also it increases the vulnerability in the society for poor people, elderly, children and women. Since this is a fairly unexplored research area, more empirical research work is needed to establish the impact of extreme weather events on health of the coastal people in Bangladesh.